Analisis Rancangan Online Market System Pasar Tanah Abang (Studi Kasus Blok F) - Aulia Paramita; Alusyanti Primawati; Lukman Lukman (Universitas Indraprasta PGRI Jakarta, 2018)
Technology users that is growing rapidly in line with the emergence of various kinds of smartphones as the mobile- and internet-based medium of communication. With the presence of the Internet and ICT, the marketing and selling processes can be conducted anytime and anywhere. Tanah Abang traditional market is one of the biggest Southeast Asian markets with complicated business activities. Many traders from inside or outside Jakarta come to the market to supply their products. Therefore, to help buyers shop by lowering their fares and to reduce traffic congestion, it is necessary to perform a research to design an online market system at Tanah Abang market, namely tenabangmarket.com. The concept of an effective modeling system is formulated by applying Grounded Research method, while the system itself is designed by using Unified Modeling Language (UML). The expected result of the research is an e-commerce system analysis in the form of online market system for traders and buyers at Tanah Abang Market, especially block F, to be next developed into the application design phas